3D graphene network encapsulating SnO2 hollow spheres as a high-performance anode material for lithium-ion batteries. Issue 9 (8th February 2017) - Hu, Xiang; Zeng, Guang; Chen, Junxiang; Lu, Canzhong; Wen, Zhenhai
Abstract : H-SnO2 @rGO with interconnected graphene encapsulating interior hollow SnO2 nanospheres is designed and fabricated, which shows outstanding lithium storage properties. Abstract : Herein, we report a reliable method for the synthesis of nanohybrids with interconnected networks of reduced graphene oxide (rGO) enwrapping hollow SnO2 nanospheres (H-SnO2 @rGO), which is implemented by an electrostatic assembly process between positively charged hollow SnO2 nanospheres and negatively charged rGO. Systematic characterizations demonstrate that the as-developed H-SnO2 @rGO has a unique three-dimensional (3D) nanostructure with favorable features for lithium ions storage, which not only provides robust protection against the aggregation and volume changes of the SnO2 nanospheres, but also ensures high transport kinetics for both electrons and lithium ions. The as-developed H-SnO2 @rGO exhibits an outstanding electrochemical performance as an anode material for lithium-ion batteries, showing a high reversible capacity of 1107 mA h g −1 after 100 cycles at a current density of 0.1 A g −1 and maintaining 552 mA h g −1 over 500 cycles at a current density up to 1 A g −1 .